A clinicomorphological study of childhood herpes zoster at a rural based tertiary center, Gujarat, India - Rita V Vora; Rahul Krishna S Kota; Nidhi B Jivani (Wolters Kluwer Medknow Publications, 2016)
Aims and Objectives: To study the clinical features of herpes zoster (HZ) in childhood along with prevalence of human immunodeficiency virus (HIV) seropositivity. Materials and Methods: The study was carried out in the Department of Dermatology at a Tertiary Care Centre of Gujarat, India, for 6 years. Children aged ≤12 years with a diagnosis of HZ seen in the Departments of Dermatology were enrolled in a predesigned pro forma. Diagnosis of HZ was made on clinical grounds, confirmed by tzanck smear as and when required. Sera of all cases were tested for HIV. Results: Total of 34 children aged ≤12 years were enrolled in the study. Nineteen (55.88%) were boys and 15 (44.12%) were girls. The mean age was 9.26 years. In 97.06% patient have localized dermatomal involvement. Most common symptom was burning pain seen in 30 (88.24%) patients. Previous history of chickenpox was present in 19 (55.88%) patients. Evidence of immunosuppression on history, clinical examination, and investigations was present only in one patient, who had HIV infection. Conclusion: Although there is increased incidence of HZ in childhood, atypical presentations are rare, multidermatomal involvement is not commonly seen. Majority of these children do not show immunosuppression. Hence, we conclude HZ in childhood occurs as a relatively mild and self-limiting disease.